eran Program Studi Manajemen Dalam Menjaga Stabilitas Ekonomi Sektoir UMKM - Wisanggeni Bagus Anggoro; Tiyan Fatkhurrokhman (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The Covid-19 pandemic has a major impact on the economic sector, especially the MSME sector which is the largest sector in the economy. Disnakerkumkm provides training for MSME facilitators to increase the capacity and ability of MSME facilitators. This training aims to increase the capacity of MSMEs accompanying MSMEs, they can provide more appropriate solutions based on theory and practice so that they can help MSMEs to rise up in the post-pandemic.